Brain Injury as a Risk Factor for Fever Upon Admission to the Intensive Care Unit and Association With In-Hospital Case Fatality: A Matched Cohort Study. (February 2015) - Rincon, Fred; Patel, Utkal; Schorr, Christa; Lee, Elizabeth; Ross, Steven; Dellinger, R. Phillip; Zanotti-Cavazzoni, Sergio
Purpose: To test the hypothesis that fever was more frequent in critically ill patients with brain injury when compared to nonneurological patients and to study its effect on in-hospital case fatality. Methods: Retrospective matched cohort study utilizing a single-center prospectively compiled registry. Critically ill neurological patients ≥18 years and consecutively admitted to the intensive care unit (ICU) with acute ischemic stroke (AIS), intracerebral hemorrhage (ICH), and traumatic brain injury (TBI) were selected. Patients were matched by sex, age, and Acute Physiology and Chronic Health Evaluation II (APACHE-II) to a cohort of nonneurological patients. Fever was defined as any temperature ≥37.5°C within the first 24 hours upon admission to the ICU. The primary outcome measure was in-hospital case fatality. Results: Mean age among neurological patients was 65.6 ± 15 years, 46% were men, and median APACHE-II was 15 (interquartile range 11-20). There were 18% AIS, 27% ICH, and 6% TBI. More neurological patients experienced fever than nonneurological patients (59% vs 47%, P = .007). The mean hospital length of stay was higher for nonneurological patients (18 ± 20 vs 14 ± 15 days, P = .007), and more neurological patients were dead at hospital discharge (29% vs 20%, P < .0001). After risk factor adjustment, diagnosis (neurological vs nonneurological), and the probability of being exposed to fever (propensity score), the following variables were associated with higher in-hospital case fatality: APACHE-II, neurological diagnosis, mean arterial pressure, cardiovascular and respiratory dysfunction in ICU, and fever (odds ratio 1.9, 95% confidence interval 1.04-3.6, P = .04). Conclusion: These data suggest that fever is a frequent occurrence after brain injury, and that it is independently associated with in-hospital case fatality.